Data and R code for estimating puma (Puma concolor) population density from clustered camera-trapping and GPS-collar telemetry monitoring using generalized spatial mark-resight models - Murphy, Sean M; Augustine, Ben C (Supplement to: Murphy, Sean M; Wilckens, David T; Augustine, Ben C; Peyton, Mark A; Harper, Glenn C (2019): Improving estimation of puma (Puma concolor) population density: clustered camera-trapping, telemetry data, and generalized spatial mark-resight models. Scientific Reports, 9, 4590, https://doi.org/10.1038/s41598-019-40926-7, 2019)
This dataset consists of a .zip folder containing all data files and R code for reproducing the spatial mark-resight analyses to estimate puma population density and abundance.